Retrospective study on early outcome of acute burn injuries treated at Nepal Cleft and Burn Centre of Public Health Concern Trust-Nepal - Rai, S M; Karki, B; Nakarmi, K; Ghartimagar, M; Nagarkoti, K; Joshi, K D; Rajbhandari, P K; Gurung, B (Journal of Nepal Health Research Council, 2015)
Background: Nepal Cleft & Burn Center, Kirtipur Hospital, Kathmandu has been providing the acute burn care since 2013 with 10 ICU beds, 32 general beds and two operating rooms. This study analyses the demographics of and  early outcome in the acute burn patients.Methods: This is a descriptive retrospective study of the clinical data of acute burn patients admitted from January 1to December 31, 2014.Results:  There were 78 patients from 3 months to 88 years of age with a median age of 29 years. Forty six (58.9%) were females and 32 (41.1%) were males. Most of the injuries (n=57; 73%) occurred inside the house. Flame burn was the commonest mode of injury (n= 48, 61.6%). Only eleven (14.1%) patients arrived on the same day of the injury. The time elapsed was from 1 to 67 days with a median of   5 days. Only two (2.5%) patients had poured water for more than 20 minutes. Range of total body surface area (TBSA) involved was 1% to 70% with a median  of 12%.Range of hospital stay was 1 to 105 days with a median of 17 days. Sixty (76.9%) patients underwent 102 surgical operations. Twenty six (33.3%) patients needed blood transfusion. A total of 15 (19.2%) patients died. None survived a burn injury of more than 40% TBSA.Conclusions: Treatment of acute burn is very challenging with high mortality rate. A lot of effort is needed  to change the present standard of care. Awareness programs on First Aid treatment of burn injuries together with the preventive programs focused on high risk population such as females and children in a large scale needs to be organized as soon as possible. Keywords: acute burn; burn injury; burn mortality; burn outcome; epidemiology.